Noninvasive Estimation of PCWP with Doppler Transmitral Flow Velocity Pattern in Patients with Coronary Artery Disease - Tamanna, RJ; Jahan, R; Akanda, AK; Reza, AQM; Zaher, A (Cardiovascular Journal, 2011)
Background: Pulmonary capillary wedge pressure is an important clinical marker of cardiac function. Recent studies have demonstrated Doppler transmitral flow velocity pattern could be useful in assessing PCWP no invasively in patient with known heart disease. Objective: The aims of the study were to correlate the Pulmonary Capillary Wedge Pressure (PCWP) estimated by Doppler echocardiography with that obtained at cardiac catheterization and to evaluate the feasibility and accuracy of Doppler echocardiographic data. Method: All patients underwent simultaneous cardiac catheterization and were studied by Doppler echocardiography. Mitral flow velocity variables & maximal left atrial volume (MLAV) were correlated with invasive PCWP by both single & multilinear regression analysis. Result: A statistically significant negative correlation of deceleration time (r=-0.483; p=0.001) and ejection fraction (r=-0.334; p=0.01) and a statistically significant positive correlation of peak E wave (r=0.345; p=0.01) and deceleration rate (r=0.651; p=0.001 were found with catheter derived PCWP. Multiple regression analysis was used to derive an equation for noninvasive estimation of PCWP. Equation. With 2-D Echo + Mitral flow variables: PCWP = 1.43 X DR + 1.32 X E/A – 0.024 X DT + .02 X MLAV + 9.2. Conclusion: The correlation coefficient between measured and estimated PCWP from the equation was (r=0.678). Data indicated that in patients with CAD the noninvasive assessment of transmitral flow velocity pattern by Doppler echocardiography could predict PCWP with a clinically meaningful degree of accuracy. Key words: Pulmonary capillary wedge pressure, Doppler echocardiography, Coronary artery disease, Cardiac catheterization. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8236 Cardiovasc. j. 2009; 1(2): 174-182